Diagnostic efficacy of endometrial aspiration cytology in women with abnormal uterine bleeding and its correlation with histopathology - Aparna,; Gupta, Veena; Pandey, Sadhana; Verma, Kachnar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Background: Abnormal uterine bleeding (AUB) is a frequent gynecological concern and a major contributor to hysterectomies. Endometrial aspiration cytology (EAC) offers a minimally invasive alternative to dilatation and curettage (D and C) for diagnosing endometrial pathologies. Objective was to assess the diagnostic efficacy of EAC in detecting underlying causes of AUB and correlate its findings with histopathological examination (HPE). Methods: A prospective analytical study involving 127 women with AUB was conducted. EAC was performed using an infant nasogastric tube, followed by D and C or hysterectomy. The cytological and histological findings were compared. Results: The mean age was 41.57±8.42 years. Heavy menstrual bleeding was the most common pattern. EAC demonstrated a sensitivity of 66.67%, specificity of 100%, PPV of 100%, and NPV of 99.07% for diagnosing malignancy. Significant cyto-histological correlation was observed (p<0.001). Conclusions: EAC is a safe, cost-effective, outpatient procedure with high specificity for detecting endometrial malignancy. It is especially useful in resource-limited settings as a first-line diagnostic tool.